Profiling antibiotic resistant bacteria and antibiotic residues in raw chicken products sold around Kenyatta University, Kenya - Daniel Ng'ang'a Kamau (Hasanuddin University, 2020)
AbstractAntibiotic resistant bacteria and antibiotic residues are a serious safety problem for animal food products. Poultry products have been long recognized as a reservoir for antibiotic resistant commensals and pathogens. Antibiotic residues ingested via food animal products expose gut micro-flora to low concentrations of antibiotics, which promote antibiotic resistance. However, there is limited knowledge regarding the potential of chicken products to act as a transmission corridor for the spread of the antibiotic resistant bacteria and antibiotic residues. The present study aimed at profiling antibiotic resistant bacteria and antibiotic residues in raw chicken products sold around Kenyatta University, Kenya. A total of 32 meat and egg samples were randomly collected from two study sites; KM and KU. Antibiotic residues in the study samples were detected using two microbiological techniques with Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Salmonella typhi as test organisms. Selective and differential media were used to isolate Escherichia coli, Salmonella and Shigella from the samples. Antibiotic susceptibility testing of these isolates against commonly used antibiotics was done using Kirby-Bauer antibiotic discs diffusion method. Of the total samples tested, 87.50% meat and 100% egg samples showed presence of antibiotic residues. The mean colony forming units (CFUs) of meat samples from KM (190.25 x 10² CFU) was higher than that of KU (104.96 x 10² CFU). Eggs from KM showed contamination (158.88 x 10² CFU) than those sampled (108.29 x 10² CFU) within the university outlets. Escherichia coli, Salmonella and Shigella, were resistant to ampicillin. Escherichia coli showed intermediate resistance to tetracycline while Escherichia coli and Shigella showed intermediate resistance to amikacin. This study reveals the presence of antibiotic residues and antibiotic resistant bacteria in chicken meat and eggs sold in the study area. Knowledge generated from this study is helps to develops effective strategies to control antibiotic resistance.Keywords: antibiotics; antibiotic resistance; antibiotic residues